Technology and assessment : the tale of two interpretations - Russell, Michael K., 1967- (Research methods for educational technology (Unnumbered), 2006)
Together, the words technology and assess-ment have different meaning for different people. Those who work with educational or instructional technology take these words to mean assessing the impacts of technology on teaching and learning. Test developers and psychometricians, however, consider ways in which computer-based technologies can be used to enhance current approaches to student assessment. This book examines technology and assessment from both perspectives by examining past, current and promising methodol-ogies and applications in both fields. The influences instructional uses of technology and the increasing reliance on testing to gauge student and school performance have on one another are also explored. The book concludes by describing an organizational structure that could bring instructional applications of technology and assessment practices into closer alignment.